Modern Information Technology in Higher Education: A Challenge to Covid-19 - Shammari, Arcelan (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
This research has conducted a survey for the modern information technology software and online learning which was carried out in Iraq and the variety of platforms used. The survey was conducted to obtain information about the use of models and platforms that were effectively used in online learning during the social distancing period to prevent the infection of COVID-19 . In addition, the information obtained from the survey also includes obstacles in the implementation of learning, how to deliver the material and the number of online meetings that are held every week. The study reached a set of conclusions, the most important of which are that the most used and influential educational platforms and software in education are Google Classroom, Zoom, Moodle and Telegram.